Zero-liquid discharge technologies for desulfurization wastewater: A review. (1st November 2022) - An, Wenhao; Zhao, Jun; Lu, Jiangang; Han, Yi; Li, Dong
Abstract: Zero-Liquid Discharge (ZLD) has received a lot of attention due to water scarcity and pollution. This article reviews the treatment of desulfurization wastewater in pretreatment, concentration and solidification with the trend of zero-liquid discharge in China. We summarize the advantages, disadvantages, performance, benefits and other characteristics of different ZLD technologies. Membrane-based technology is an effective means of recycling wastewater in ZLD systems. Therefore, we focus on the application of bipolar membrane electrodialysis (BMED) in desulfurization wastewater and high-salt wastewater treatment, discussing its limitations and solutions. In addition, several Chinese ZLD cases and economic analysis are introduced. It is believed that ZLD will become a new trend in desulfurization wastewater treatment in the future. Therefore, exploring new materials and technologies with low cost and high efficiency is the focus of future work. Highlights: Zero-liquid discharge technologies for desulfurization wastewater are compared. The applications of bipolar membrane technology in wastewater treatment are emphasized. Economic analysis of several industrial cases is made.